Termination of reperfusion arrhythmia by coronary artery occlusion. Issue 1 (July 1994) - Grech, E D; Ramsdale, D R
Abstract : Reperfusion arrhythmias may be a cause of sudden death in acute myocardial infarction. A patient underwent successful coronary artery recanalisation by primary percutaneous transluminal coronary angioplasty (PTCA) for acute myocardial infarction. In this patient an idioventricular rhythm with a severe haemodynamic effect developed within one minute of deflation of the PTCA balloon. Sinus rhythm was immediately restored by reinflating the balloon and thus reinterrupting the supply of oxygenated blood. This suggests that reperfusion with consequent reoxygenation is a primary factor in arrhythmogenesis.